Empowering Women Through Entrepreneurship in the Digital Era to Achieve Economic Independence - Rina Mudjiyanti; Ika Yustina Rahmawati; Rifka Arofah; Ira Hapsari; Nur Isna Inayati (Universitas Muhammadiyah Purwokerto, 2025)
This community service aims to increase the self-confidence, self-development, and entrepreneurial skills of Aisyiyah women to strengthen the community's economy. Support from the local and central government is essential for this activity. Situational analysis shows that the obstacles faced are limited capital, narrow mindsets, and fear of failure in opening and running a business. This empowerment activity is carried out through training and mentoring in business development, financial management, and product marketing. The results of this activity show an increase in self-confidence and entrepreneurial skills among Aisyiyah women. This increase is measured through the economic growth of their businesses and the increase in product marketing reach. The discussion emphasizes the importance of the mental toughness of an entrepreneur to survive in a declining economy. Good and structured planning and optimal use of technology play an important role in business development. This activity has a positive impact on developing Aisyiyah women's businesses and creating financially independent women.